Management of resistant supraventricular tachycardia in the immediate postpartum period: A case report - Gangadharaiah Narasimhaiah; Nataraj M Srinivasan; Aruna Hemadribotla; Renuka Ramaiah (Wolters Kluwer Medknow Publications, 2013)
Supraventricular tachycardia (SVT) during pregnancy or immediate postpartum is the commonest arrhythmia during pregnancy. Usually, the clinical symptoms are mild or go unrecognized. Rarely as in our case, can patient present with severe symptoms of agitation and restlessness which can mimic puerperal psychosis. A 12 lead electrocardiogram (ECG) and an echocardiogram usually are sufficient to diagnose SVT. Amiodarone, even though is not the drug recommended to be used during pregnancy, in resistant types of SVT it is an useful drug.